Number of spanning Trees in the sequence of some Nonahedral graphs - Daoud S.N. (Utilitas Mathematica, 2020)
A nonahedral graph is a polyhedral graph having nine vertices. In this work, using knowledge of difference equations we drive the explicit formulas for the number of spanning trees in the sequence of some Nonahedral graphs such as Fritsch graph, Tridiminished icosahedron graph and (93) - configuration graph 2 by electrically equivalent transformations and rules of weighted generating function. Finally, we compare the entropy of our graphs with other studied graphs with average degree being 4,5 and 6. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.